Humanism Against Bullying in Sohn Won Pyung’s Almond Novel - Magdalena Ivena Angeline; Maria Eka Mulatsih (CV. Global Health Science Group, 2022)
Korean Pop culture has millions young followers around the world including Indonesian. Starting from music, Korean style also emerges in the form of its drama and novel. One of valuable Korean works which is worth to analyze is Almond. Beside this novel has been translated into 13 different languages, it contains humanism values. This study reveals humanism classifications in Almond by applying a theory proposed by Copson (2015). Since this study deals with literature, library research is applied. The researchers collected the data from the novel by reading and highlighting parts based on Humanism theory. After that, the results of classification were analyzed using formalism approach and delivered qualitatively. This research found that Yoon Jae, the main character, fulfills most of the classifications of humanism, namely starting with human being, valuing truth, death, tragedy, the pursuit of happiness, personal development, making connections, the origins of morality, and the aim of morality in the story. Some of the humanism classifications were reflected in Yoon Jae when experiencing bullying, namely: valuing truth, having personal development, and making connections. He managed to get through bullying when he started to feel the pursuit of happiness and when he started doing the aim of morality. Yoon Jae's humanism action managed him to survive from bullying and to continue his life like an ordinary person.